ANALISA MENGENAI PEMBERIAN FASILITAS KREDIT MODAL KERJA OLEH BANK MELALUI MEKANISME “TAKE OVER” (Kajian Mengenai Prosedur Dan Jaminan Pada Bank Swasta Di Medan) - MARIANA MARIANA (PREMISE LAW JURNAL, 2015)
Working capital is the credit for individual and business entity as the addtional capital for developing the running business. The government encourages, supports, and helps UKM ( Small and Medium Enterprise ) sector in order that it can support the Indonesian economic system. It indicates that the government wants the Indonesian economy to develop, especially through UKM sector. One of the efforts made by the government is guaranteeing UKM development is the access to the guarantee in providing financing which includes banking credit. Bank as credit provider competes openly in offering its credit; one of its stategies is attracting its debtors who comes from other banks which have track record in good credits so that the banks has qualified debtors and can minimize nonperfoming loan. This strategy is “take over” credit. Keywords: Working Capital Credit, Credit Transfer, Take Over